A rare case of adolescent tuberculous pericardial effusion: a case report - Primanelza, Dewi Hanifa; Pramudita, Arvin; Mansyoer, Riza (International Journal of Advances in Medicine, 2022)
Tuberculous pericarditis (TBP) is a rare case of extrapulmonary TB (EPTB) especially in the developed countries. This may cause serious and deadly impact if not diagnosed and treated properly. A-15-year-old girl was admitted with tightness of breath, weight loss, a productive cough and fatigue. Severe malnutrition, bronchial rales and anemia are present in patient. Chest x-ray showed pleural effusion with cardiomegaly. On three days later, Thoracic multi-slice spiral (MSCT) confirmed pericardial effusion, following pericardiocentesis on the fifth day. Tuberculous was confirmed by analysis of pericardial fluid. This patient was diagnosed as tuberculosis pericardial effusion showed complete recovery after pericardiocentesis and anti-tuberculosis drugs administration. Tuberculous is an endemic disease and its extrapulmonary forms should be included as a differential diagnosis. Early and adequate treatment decreases the risk of developing into a potentially fatal disease.